2013
DOI: 10.1002/htj.21116
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gaseous Flow Between Parallel Plates by Second‐ Order Velocity Slip and Temperature Jump Boundary Conditions

Abstract: In this study the momentum and energy equations are solved to analyze the flow between two parallel plates by employing second-order velocity slip and temperature jump conditions. The flow is considered to be laminar, incompressible, hydrodynamically/thermally fully developed, and steady state. In addition to the isoflux condition, viscous dissipation is included in the analysis. Closed form expressions for the temperature field and Nusselt number are obtained as a function of the Knudsen number and Brinkman n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…It is observed that the temperature jump has an antagonist effect compared with velocity slip as far as heat transfer is concerned. The effect of second-order velocity slip and temperature jump boundary conditions on the heat transfer characteristics of gaseous flow between isoflux micropipe/parallel plates has been reported elsewhere [44,45]. The present study intends to quantify the influence of second-order velocity slip, viscous dissipation, and different heat fluxes boundary conditions on heat transfer characteristics of hydrodynamically and thermally fully developed flow between parallel plates.…”
Section: Theoretical Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…It is observed that the temperature jump has an antagonist effect compared with velocity slip as far as heat transfer is concerned. The effect of second-order velocity slip and temperature jump boundary conditions on the heat transfer characteristics of gaseous flow between isoflux micropipe/parallel plates has been reported elsewhere [44,45]. The present study intends to quantify the influence of second-order velocity slip, viscous dissipation, and different heat fluxes boundary conditions on heat transfer characteristics of hydrodynamically and thermally fully developed flow between parallel plates.…”
Section: Theoretical Analysismentioning
confidence: 95%
“…Numerous second-order slip models [37][38][39][40][41][42][43] were proposed to analyze the fluid flow and heat transfer characteristics with the choice of different slip coefficients. Recently, closed form expressions were stated for the Nusselt number using second-order velocity slip and temperature jump condition [44,45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While, the fully developed Nusselt number does not vary significantly with the change in the thermophysical properties in the analysis [34,35]. Efforts have been made to study the effect of second order boundary conditions and asymmetric heat flux boundary conditions on the heat transfer characteristics of various geometries such as: parallel plate microchannels and micropipe [36][37][38]. It is observed that the asymmetric heat flux condition significantly alters the temperature profile and singularities in Nusselt number are obtained for various values of Knudsen number [18][19][20].…”
Section: Introductionmentioning
confidence: 86%
“…It is reported that velocity slip and temperature jump affect the heat transfer performance in opposite ways [15]. Also, the studies report the deviation in heat transfer performance by considering the first and second order slip models [36][37][38]. The effect of asymmetric heat flux ratio on the heat transfer ratio and the heat transfer performance has also been reported [9,[18][19][20].…”
Section: Introductionmentioning
confidence: 87%